2020
DOI: 10.1002/stem.3183
|View full text |Cite|
|
Sign up to set email alerts
|

TGF-β secreted by human umbilical cord blood-derived mesenchymal stem cells ameliorates atopic dermatitis by inhibiting secretion of TNF-α and IgE

Abstract: Human mesenchymal stem cells (MSCs) are promising therapeutics for autoimmune diseases due to their immunomodulatory effects. In particular, human umbilical cord blood-derived MSCs (hUCB-MSCs) have a prominent therapeutic effect on atopic dermatitis (AD). However, the underlying mechanism is unclear. This study investigated the role of transforming growth factor-beta (TGF-β) in the therapeutic effect of hUCB-MSCs on AD. Small interfering RNA (siRNA)-mediated depletion of TGF-β disrupted the therapeutic effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 82 publications
(173 reference statements)
1
33
0
Order By: Relevance
“…Dysregulation of MC functions can contribute to the initiation and progression of various pathological conditions or diseases such as allergic and anaphylactic reactions, abnormal wound healing, fibrosis, and malignancies (79). Several lines of evidence have shown that MSCs can also modulate MC activation and functions (80)(81)(82)(83)). An early study showed that murine BMSCs effectively suppressed MC degranulation, pro-inflammatory cytokine production, chemokinesis and chemotaxis when co-cultured with direct cell-cell contact in vitro and following in vivo administration in a model of passive cutaneous anaphylaxis and a peritoneal degranulation assay (83).…”
Section: Mast Cellsmentioning
confidence: 99%
“…Dysregulation of MC functions can contribute to the initiation and progression of various pathological conditions or diseases such as allergic and anaphylactic reactions, abnormal wound healing, fibrosis, and malignancies (79). Several lines of evidence have shown that MSCs can also modulate MC activation and functions (80)(81)(82)(83)). An early study showed that murine BMSCs effectively suppressed MC degranulation, pro-inflammatory cytokine production, chemokinesis and chemotaxis when co-cultured with direct cell-cell contact in vitro and following in vivo administration in a model of passive cutaneous anaphylaxis and a peritoneal degranulation assay (83).…”
Section: Mast Cellsmentioning
confidence: 99%
“…Genetic predisposition, environmental factors, and immunological abnormalities all influence the onset of atopic dermatitis, although the complex pathogenesis remains incompletely understood. In their new STEM CELLS article, Park et al explore the mechanisms by which MSC‐secreted TGF‐β modify the symptoms of atopic dermatitis 3 . The subcutaneous administration of hUCB‐MSCs in a mite allergen‐induced mouse model of atopic dermatitis fostered beneficial alterations to histopathology, mast cell infiltration, tumor necrosis factor‐alpha (TNF‐α) expression, and serum immunoglobulin E (IgE) levels.…”
Section: Featured Articlesmentioning
confidence: 99%
“…MSCs derived from the umbilical cord or adipose tissue represent a readily available and patient‐matched source of immunomodulatory cells that have been assessed at the preclinical and clinical levels in various diseases/disease models; however, we still lack a deep understanding of the mechanisms involved in TGF‐β‐mediated immunomodulation. In our first Featured Article published this month in STEM CELLS , Park et al describe the TGF‐β‐mediated immunomodulatory mechanisms that mediate the alleviation of atopic dermatitis, a chronic allergic skin disorder, following the subcutaneous administration of human umbilical cord blood‐derived MSCs (hUCB‐MSCs) 3 . In a Related Article published recently in STEM CELLS Translational Medicine , Noh et al reported that TGF‐β secreted by MSCs polarized microglia, the macrophages of the central nervous system, from a classically‐activated phenotype into an inflammation‐resolving phenotype to inhibit the neuroinflammatory processes associated with neurodegenerative disorders 4 …”
mentioning
confidence: 99%
“…MSCs facilitate neurological recovery and neo-angiogenesis through the secretion of neurotrophins and angiogenesis regulatory factors [8][9][10]. The ability of immunomodulatory effect, migratory capability, and regenerative potential of MSCs are confirmed in multiple disease models, such as atopic dermatitis, myocardial infarction, traumatic brain injury, and diabetes nephropathy [11][12][13][14]. However, accumulating researches suggest that the biodistribution of MSCs in the target organs is rare, and its therapeutic effect appears to be a consequence of the paracrine action [15][16][17].…”
Section: Introductionmentioning
confidence: 99%